Synura korshikovii sp. nov. (Chrysophyceae, Synurales), a new species from Ukraine - Kapustin, Dmitry; Gusev, Evgeniy (Phytotaxa, 2015)
A new species, Synura korshikovii sp. nov., is described from water reservoirs in the vicinities of Polisky Nature Reserve, Northern Ukraine, based on scale morphology studied by means of transmission and scanning electron microscopy. This species has three types of scales: spine-bearing oval body scales, spine-bearing prolonged transition scales and spineless ovate or circular caudal scales. All scale types are covered with hexagonal reticulum. The spine is clavate or cylindrical with flat apex terminating in a few rows of papillae-like teeth.